PROFIL LEGISLATIF PEREMPUAN PERIODE 2004-2009 DI DPRD PROPINSI JAWA TENGAH - Astuti, Puji (JURNAL ILMU SOSIAL, 2013)
Woman in legislative still be debated until now, connecting both with quantity or quality. There still much negative perception which was not favourable for woman to get involve actively as a member of legislature. On reality, the amount of woman in Indonesia more than half of our population, so it was realistic if woman get more active in political process. The more woman in legislative election because of politics, econimics or socil constraints. Thus research also had proved that although woman have capacity, the path to get political office on legislative still be hard struggle, mainly because of high political cost should be paid.